Nodeless superconducting gap in the caged-type superconductors Y5Rh6Sn18 and Lu5Rh6Sn18. (28th August 2015) - Zhang, Z; Xu, Y; Kuo, C N; Hong, X C; Wang, M X; Cai, P L; Dong, J K; Lue, C S; Li, S Y
Abstract: Low-temperature thermal conductivity measurements were performed on the single crystal of caged-type superconductors Y5 Rh6 Sn18 and Lu5 Rh6 Sn18 down to 80 mK. In zero magnetic field, no residual linear term is found for either superconductor. At low field, the of these two superconductors shows weak field dependence. These results exclude the nodal superconducting gap in Y5 Rh6 Sn18 as revealed by recent specific heat measurements, and suggest that the caged-type superconductors R5 Rh6 Sn18 (R = Y and Lu) may have a common nodeless superconducting gap.